Communication With Students - Knez, Jana; Knez, Sandi (Organizacija in organiziranje, 2025)
In this paper, we aim to present the field of communication and communication with the selected target group. In an era of generational change, there are specificities that are not only reflected in the communication during the teaching process but also in the communication perceived in students' application and enrolment procedures and in the management of other activities related to their studies. We want to present the advantages and obstacles in communication, highlighting the specificities of communication through online tools and the elements of successful communication.